Recent Advances of Telepractice for Autism Spectrum Disorders in Speech and Language Pathology - Christopoulou, Maria; Drosos, Konstantinos; Petinou, Kakia (My University, 2022)
Telepractice or teletherapy is defined as the means of service delivery via technology-based platforms that allow long-distance interventions across populations, age spans, and geographical locations. Specifically, telepractice capitalizes on communication technologies such as online modules, videoconferencing, and computerized software programs, in servicing populations with communication challenges. Notably, telepractice has emerged as a potentially effective, low-cost, and promising means of conducting and completing online assessment, diagnosis, and intervention sessions for individuals with autism spectrum disorders (ASD). Moreover, telepractice allows the inclusion of parents, caregivers, and educators as potential facilitators in supporting treatment delivery in populations with ASD. This thematic review article aims to highlight and acquaint practitioners and other stakeholders with relatively recent information regarding the advantages and disadvantages of the telepractice service delivery model in ASD. Furthermore, the emergence of the COVID-19 pandemic has impacted service delivery in the field of Health Sciences including speech and language pathology (SLP). Consequently, the need to avoid face-to-face therapy sessions, recommended to SLPs as to all health practitioners, resulted in the call for adaptation and adjustment of service telepractice. This paper attempts to answer this call by suggesting supplementing traditional diagnostic and therapy resources with training modules consisting of online materials and use of animated and specially designed programs in SLP intervention with individuals with ASD. Lastly, the paper includes a discussion of research findings in the field, a conclusion, and a take-home message.
Keywords: ASD; assessment; interventions; tele-supervision; telepractice